Analisis Akuntabilitas, Transparansi dan Efisiensi Terhadap Produktivitas Sekolah Kecamatan Polokarto - Nugroho, Totok Susilo Pamuji (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to examine the effect of accountability, transparency and efficiency of financial management on school productivity in senior high school in Polokarto sub-district. This type of research is quantitative. The population in this study were 120 educators in senior high school in Polokarto sub-district. The sample in this study used purposive sampling method and obtained 50 educators in senior high school in accordance with predetermined criteria. The data analysis technique used is multiple regression analysis with SPSS 16.0 program. The results showed that the variables of accountability and transparency had no effect on school productivity. Meanwhile, the variable of financial management efficiency has an effect on school productivity.